Applications of metamaterial sensors: a review - Prakash, Divya; Gupta, Nisha (International journal of microwave and wireless technologies, 2022)
Sensors based on metamaterial absorbers are very promising when it comes to high sensitivity and quality factor, cost, and ease of fabrication. The absorbers could be used to sense physical parameters such as temperature, pressure, density as well as they could be used for determining electromagnetic properties of materials and their characterization. In this work, an attempt has been made to explore the various possible applications of these sensors. Metamaterial-based sensors are very popular for its diverse applications in areas such as biomedical, chemical industry, food quality testing, agriculture. Split-ring resonators with various shapes and topologies are the most frequently used structures where the sensing principle is based on electromagnetic interaction of the material under test with the resonator. Overcoming the design challenges using metamaterial sensors involving several constraints such as cost, compactness, reusability, ease in fabrication, and robustness is also addressed.